The Influence of Entrepreneurship Education, Family Environment, and Self-efficacy on Entrepreneurial Interest of Class XI Students of SMA Negeri 3 Semarang - Namira Adinda Salsafatikha; Via Amalia (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of entrepreneurship education, family environment, and self-efficacy on the entrepreneurial interest of eleventh-grade students at SMA Negeri 3 Semarang. The study is motivated by the high unemployment rate among the productive-age population and secondary education graduates in Indonesia, indicating the need for strategic efforts through strengthening entrepreneurship education at the secondary education level. This study employed a quantitative approach with an explanatory research design. The research population consisted of 412 eleventh-grade students of SMA Negeri 3 Semarang in the 2025/2026 academic year who had completed the Craft and Entrepreneurship (PKWU) subject, with a sample of 203 students selected using proportional random sampling techniques. Data were collected through questionnaires and observations, while data analysis was conducted using the Partial Least Square (PLS) method. The results showed that all variables met the validity and reliability criteria. The R-Square value of 0.705 indicates that entrepreneurship education, family environment, and self-efficacy were able to explain 70.5% of entrepreneurial interest. Hypothesis testing showed that entrepreneurship education had a positive and significant effect on entrepreneurial interest (β = 0.357; p = 0.000), family environment had a positive and significant effect on entrepreneurial interest (β = 0.206; p = 0.003), and self-efficacy had a positive and significant effect on entrepreneurial interest (β = 0.393; p = 0.000). The findings indicate that educational factors, family support, and individuals’ confidence in their own abilities play an important role in increasing students’ entrepreneurial interest.